Analyzing the Objectives of Shariah as intended by the Lawgiver in enacting Shariah (Text) for Ifhām (Proper Understanding) according to al-Shatibi - Rabbani, Arif (Penerbit Universiti Kebangsaan Malaysia, 2022)
An in-depth knowledge of the Objectives of Shariah, as intended by Allah the Lawgiver, is needed for analytical research when enacting Shariah. The question arises regarding the level of Arabic language knowledge required to understand Shariah before one is considered bound by Shariah injunctions. The main aim of this study is to elaborate on the classification of the Objectives of Shariah as advanced by al-Shatibi, especially, the objective of enacting Shariah for proper understanding (Ifhām). Also discussed in this study are the identification of foreign terms introduced into the Arabic language, if any found in the Quran, the knowledge of rules relating to customary usage of Quranic Arabic as understood by both laymen and experts, and the role these play in deducing the objectives of enacting Shariah. Another objective of Islamic law is the secondary connotation, whereby each interpreter understands the same text differently. This is the basis for translated text of Shariah. The findings of this study reveal that, firstly, there are no non-Arabic terms in Shariah text; second, Shariah text have both primary and secondary connotations which pose problems in translation; third, the Arabic language text was revealed to an unlettered Arab who understood it and implemented the demands of the text; fourth, there are linguistic maxims from which objectives result, as raised by al-Shatibi; finally, al-Shatibi re-defined in detail both primary and secondary connotations of Sharia texts due to their significance, since command and prohibition verses may independently convey such injunctions.